Gendered experiences of appearance-related perks and penalties in Finnish labor markets - Kukkonen Iida; Sarpila Outi (The Royal Danish Library, 2022)
Physical appearance is generally associated with considerable labor-market sanctions, and appearances are thought to be of particular importance in the feminine service sector. However, little is known about workers’ experiences of appearance-based perks and penalties in Nordic labor markets. Drawing on literature on aesthetic capital and labor, this study aims to fill this research gap. The study uses a nationally representative survey (N = 1600) fielded in Finland and multinomial regression to determine whether subjective experiences of appearance-related perks and penalties are gendered, dependent on the field of work or daily work on appearances. Our main finding is that while both men and women experience looks-based perks and penalties, men are more likely to have experienced appearance having a say in salary negotiations. Our results shed light on the gendered logics of aesthetic capital and labor, and question economic understandings of beauty work as a pathway to labor market success for women